PENGARUH MODEL PBL BERBASIS MULTILITERASI TERHADAP PEMAHAMAN SISWA LEWAT ISI BACAAN PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD - Vahira Agustin Ainia; Rarasaning Satianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was carried out with the primary goal of identifying a notable impact stemming from the utilization of problem-based learning models that are grounded in multiliteracy. Within the framework of multiliteracy-based problem- based learning, students are actively encouraged to tackle problems by employing a diverse set of literacy proficiencies, encompassing reading, writing, listening, and speaking. The methodological approach adopted for this study involved a quasi-experimental design, employing both pre-tests and post-tests administered to students in both the control and experimental groups; the participants in this research consisted of students from grades V-A and V-B at SDN Dukuh Menanggal I/424 Surabaya. The collection of research data was achieved through the administration of pre-tests and post-tests, which were completed by the students themselves. The data analysis techniques implemented incorporated essential prerequisite tests, which included normality tests, homogeneity tests, as well as hypothesis tests. The findings of the study indicated that the implementation of a multiliteracy-based problem-based learning model does, in fact, exert an influence on students' comprehension of reading content. The application of this pedagogical model has the potential to enhance students' understanding of the material they read, particularly in areas such as reading comprehension, analytical skills, and the ability to critically evaluate information. Furthermore, the deployment of this model is capable of optimizing students' competencies when it comes to articulating opinions, ideas, and concepts in a manner that is both more organized and structured. Keywords: Multiliteracy-based PBL Model, Student Understanding